2019
DOI: 10.2196/12157
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying Breastfeeding for Fathers: Process Evaluation of the Milk Man Mobile App

Abstract: Background Mobile technology offers unique opportunities to reach people with health promotion interventions. Breastfeeding is an important public health issue, and fathers are a key support. Milk Man is a father-focused breastfeeding app that sought to engage fathers with information and conversation about breastfeeding, with the goal to impact positively on breastfeeding duration. Objective The study aimed to describe the process evaluation of the Milk Man app that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
0
27
0
6
Order By: Relevance
“…Walsh et al [60] in their study involving Australian father-infant dyads reported a strong association between fathers' and children's intake of snacks and SSBs. The association observed in the current study demonstrates the prospective significance of including fathers or partners in interventions targeted towards improving infant feeding practices [61].…”
Section: Predictors Of Early Introduction Of Discretionary Foodsmentioning
confidence: 52%
“…Walsh et al [60] in their study involving Australian father-infant dyads reported a strong association between fathers' and children's intake of snacks and SSBs. The association observed in the current study demonstrates the prospective significance of including fathers or partners in interventions targeted towards improving infant feeding practices [61].…”
Section: Predictors Of Early Introduction Of Discretionary Foodsmentioning
confidence: 52%
“…Participants expressed a need to have choice of delivery modes, for example, telephone calls or text messages or combination of both. Their views are similar to those expressed by participants in other obesity prevention programs that suggest innovative approaches to delivering interventions [35], where text messages were considered as supplementary to telephone coaching calls [12,17,34], or where participants preferred a combination of telephone calls and/or emails with social media or online platforms due to changing needs and to enhance engagement [8][9][10]38].…”
Section: Discussionmentioning
confidence: 62%
“…These interventions primarily focus on one or more behaviours such as breastfeeding, introduction of solids and physical activity. However, the mode of delivery of interventions differs between trials, for example: face-to-face via home visits [1,2]; face-to-face via parent groups in the community [3,4]; face-to-face via child care settings [5][6][7]; via internet [8]; via mobile applications or apps [9][10][11]; via text messages [12] and via telephone calls or/and text messages [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, PIFI is the largest breastfeeding intervention targeting fathers. We have previously reported on the process evaluation of the interventions and demonstrated that each interventions in terms of intent, content, and delivery was feasible, useful, and acceptable to fathers [ 34 , 39 , 50 ]. We were, however, unable to demonstrate impact of a face-to-face or mHealth intervention, either individually or in combination, on infant feeding outcomes, maternal breastfeeding self-efficacy, or level of postpartum partner support.…”
Section: Discussionmentioning
confidence: 99%
“…As this was the first app of its kind designed especially for fathers, there is no other study to compare it with. However, an extensive process evaluation of the app was undertaken as part of the PIFI [ 50 ] using a comprehensive and customized evaluation framework, which in addition to determining the impact and efficacy of the app, also examined elements such as the robustness of the technology, the intervention principles and engagement strategies, and the interaction of the user with the technology [ 57 ]. The design and ease of use of the app rated highly, and overall, users’ opinions of the app were positive, with two-thirds indicating that they would recommend the app to other fathers [ 50 ].…”
Section: Discussionmentioning
confidence: 99%